A survey of optometrists' ophthalmic medication prescribing - Gonzalez AL; Bennett N; Lakhani R (Clinical Optometry, 2014)
Agustin L Gonzalez, Nikki Bennett, Rakesh Lakhani Inter American University, School of Optometry, Bayamón, Puerto Rico Abstract: Optometry is recognized as a primary care profession within the health care system. For years, much emphasis has been placed on the core function of optometrists as prescribers for refractive correction, yet little is known about their medication prescribing habits. Optometrists have had the ability to prescribe medications for the last 30 years, and still little information is available about optometric pharmaceutical trends. This study consists of a survey aimed at obtaining self-reported data to depict optometrists' likelihood of prescribing ophthalmic medications during a regular clinic day. We conclude that optometrists are indeed using medications in their clinics, and the trends are very similar to the epidemiological distribution of eye disorders in the general population. Keywords: optometry, prescription drug audit, pharmacoepidemiology